Hepatocellular carcinoma in a patient with acute intermittent porphyria: importance of digestive follow-up. - C Alonso Belmonte; B Parra-López; MI Sánchez Sánchez; M Jiménez Pérez; AM Bravo Aranda (Revista Andaluza de Patología Digestiva, 2026)
Abstract Acute intermittent porphyria (AIP) is a rare metabolic disorder with autosomal dominant inheritance and low penetrance that may be associated with severe long-term hepatic complications, including hepatocellular carcinoma (HCC), even in the absence of liver cirrhosis. We present the case of a 76-year-old woman with a previous diagnosis of AIP and stage IV chronic kidney disease, without regular follow-up by the gastroenterology department. During an abdominal ultrasound performed as part of her nephrological follow-up, a large hepatic mass was incidentally detected. Further evaluation with computed tomography and contrast-enhanced magnetic resonance imaging revealed an 8-cm lesion in segment VII with imaging features consistent with hepatocellular carcinoma (LI-RADS 5), arising in a non-cirrhotic liver. Histological confirmation was obtained after biopsy, which was complicated by a perihepatic hematoma. Due to age and comorbidities, curative treatments were ruled out; transarterial chemoembolization (TACE) and transarterial radioembolization (TARE) were also considered non-curative locoregional options in this setting, and systemic therapy with sorafenib was initiated. Patients with AIP have an increased risk of developing HCC, regardless of the presence of cirrhosis, particularly after the age of 50. Lack of structured digestive and hepatological follow-up may delay diagnosis and limit therapeutic options. Regular follow-up by gastroenterology and hepatology, including periodic liver imaging, is essential in patients with AIP to enable early detection of hepatocellular carcinoma and improve clinical outcomes.